Building portals intranets, and corporate web sites using microsoft servers - Townsend, James J. (Addison-Wesley, 2004)
Guide to designing, developing, and implementing Web portals using Microsoft servers and the .NET Framework. Shows how to create a portal architecture based on Microsoft .NET and integrate multiple server technologies and components to create a powerful portal solution. Softcover. DLC: Web portals--Design.